Hemoglobin Status of the Hospital Admitted Patients: A Cross-Sectional Study in A District Hospital of Bangladesh (TAJ: Journal of Teachers Association, 2022)
Introduction: Anemia is a global public health concern, especially in lower and middle income countries like Bangladesh. The present study aimed to find out the hemoglobin level and prevalence of anemia among the patients admitted in a district hospital of Meherpur, Bangladesh.Methods: This cross sectional study was conducted among 500 patients admitted to Medicine and Gynecology department of Meherpur General Hospital. After enrollment, 2-3 ml of blood sample was collected in EDTA tubes from each patients and hemoglobin level was determined using an automated hematology analyzer for determination of anemia as defined by the WHO. All statistical analyses were carried out using SPSS version 24.0 for a significant p-value